High-pressure processing and heat treatment of Murrah buffalo milk: comparative study on microbial changes during refrigerated storage - Yu, Darren Sim Xuan; Hui, Chong Kah; Ismail Fitry, Mohammad Rashedi; Koirala, Pankaj; Nirmal, Nilesh; Mahmud Ab Rashid, Nor Khaizura (Elsevier B.V., 2025)
This study aims to evaluate the effect of high-pressure processing (HPP) (500 and 600 MPa for 3 min and 5 min) on the microbial changes of Murrah buffalo milk in comparison to heat treatment (72 °C for 15 s of holding time) during refrigerated storage of 28 days. The results indicated that the total plate count (TPC) of raw milk at day 0 was 5.5 ± 0.6 log10 CFU/mL. At day 0, heat treatment lowered TPC to 3.9 ± 0.6, while HPP treatment was in the range of 4.1 ± 0.3 to 4.8 ± 0.6 log10 CFU/mL. Similarly, lowered yeast and mold count and lactic acid bacteria were noted in heat- and HPP-treated milk samples compared to the control sample during refrigerated storage. There were no Staphylococcus aureus and Escherichia coli detected in heat and HPP-treated samples. Heat or HPP treatment at 600 MPa for 5 min significantly extended the shelf-life of Murrah buffalo milk for three weeks at the refrigerated storage. In addition, HPP treatment did not alter the pH, lightness (L* value), protein, or fat content of Murrah buffalo milk during refrigerated storage. Hence HPP at 600 MPa for 5 min could be a suitable alternative to conventional heat treatment.